1979
DOI: 10.1080/00039896.1979.10667411
|View full text |Cite
|
Sign up to set email alerts
|

Immunological Alterations in the Lungs of Mice following Ozone Exposure: Changes in Immunoglobulin Levels and Antibody-Containing Cells

Abstract: Ozone was added to the air of the environmental chambers containing specific pathogen-free mice. At levels of 0.5 and 0.8 ppm the oxidant was seen to have inflammatory effects, as shown by rising serum albumin levels in lung lavage fluid. Fluorescein conjugated anti-heavy chain sera were used to detect cells containing IgM, IgG, and IgA in measured lung areas termed Pulmonary Units. Antigenic stimuli occurred along the airways, with significant increases of IgA-containing cells in the bronchus-associated lymph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

1981
1981
2000
2000

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 15 publications
1
19
0
Order By: Relevance
“…IgG-and IgM-secreting cells in murine bronchus-associated lymphoid tissue (BALT) (9) and B-cell numbers in the lung as a whole did not change with prolonged 03 exposures (7). Likewise, exposure of rats to 0.13 ppm 03 for 1 week increased T/B cell ratios in the MLN, with the increases lasting for at least 5 days after cessation of exposure (10).…”
Section: Environmental Health Perspectivesmentioning
confidence: 96%
“…IgG-and IgM-secreting cells in murine bronchus-associated lymphoid tissue (BALT) (9) and B-cell numbers in the lung as a whole did not change with prolonged 03 exposures (7). Likewise, exposure of rats to 0.13 ppm 03 for 1 week increased T/B cell ratios in the MLN, with the increases lasting for at least 5 days after cessation of exposure (10).…”
Section: Environmental Health Perspectivesmentioning
confidence: 96%
“…It has also been reported that O 3 and NO 2 exposure can alter the pattern of the immunological response [136,[143][144][145][146][147]. An increased level of immunoglobulins in lung lavage fluid has been reported in mice after exposure to O 3 [143].…”
Section: Defence Against Infectionsmentioning
confidence: 99%
“…It has also been reported that O 3 and NO 2 exposure can alter the pattern of the immunological response [136,[143][144][145][146][147]. An increased level of immunoglobulins in lung lavage fluid has been reported in mice after exposure to O 3 [143]. In guinea-pigs, the appearance of serum antibody to normal lung tissue relates to the amount and duration of exposure to NO 2 , possibly as a consequence of an auto-antigenic effect of altered components of the lung tissue [144].…”
Section: Defence Against Infectionsmentioning
confidence: 99%
“…Our previous work had shown that damage to respiratory mem branes could be monitored by quantitating the serum albumin levels in respiratory se cretions [3]. On day 4 of ozone exposure a peak of serum albumin in secretions sug gested that this was a period of impaired membrane integrity, and a time when ex trinsic antigen might easily gain access to immunocompetent cells in the mesenchymal tissues underlying the epithelium.…”
Section: Discussionmentioning
confidence: 99%
“…Osebold et al [3] found that ozone in concentrations that are achieved in high air pollution episodes can effect changes in the lungs of mice, including immunological re sponsiveness. Oxidant damage by ozone was accompanied by increases of IgA-containing cells in the lungs and rises in the IgA content of respiratory secretions.…”
Section: Introductionmentioning
confidence: 99%